Oldtidens ansigt. Faces of the Past. Til Hendes Majestæt Dronning Margrethe II 16. april 1990. (I kommission hos Poul Kristensen Forlag, 1990). 208 s., 295 kr. - Christiansen, Erik (Historie/Jyske Samlinger, 1991)
-